Commentary: The dynamic panel model: a promising approach to clarify sources of influence in developmental psychopathology – a commentary on Wichstrøm et al. (2017). (23rd October 2017) - Klein, Annette M.; Bergmann, Sarah; White, Lars O.
Abstract : In their study, Wichstrøm et al. (2017) have proposed a novel groundbreaking approach for developmental psychopathology that undoubtedly will inspire other research. Applying the dynamic panel model (DPM), the authors were able to show that within‐disorder (homotypic) and between‐disorder (heterotypic) continuities of psychiatric symptoms are mostly due to unmeasured time‐invariant factors while only few effects of earlier symptoms on later symptoms remained significant after accounting for these factors. The DPM calls for future applications of this approach to samples across different countries, diverse developmental phases, and in various settings – community samples and clinical samples alike. Abstract : Read the full article at doi:10.1111/jcpp.12754